A case-control study of influenza vaccine effectiveness among Malaysian pilgrims attending the Haj in Saudi Arabia - Mustafa, Amal Nasir (Elsevier, 2003)
Objectives: To determine influenza vaccine effectiveness against clinically defined influenza-like illness among Malaysian pilgrims attending the Haj in Saudi Arabia.